Streptococcus pneumoniae carriage studies in adults: Importance, challenges, and key issues to consider when using quantitative PCR-based approaches - Miellet, Willem R.; Almeida, Sónia T.; Trzciński, Krzysztof; Sá-Leão, Raquel (Frontiers in Microbiology, 2023)
Streptococcus pneumoniae causes significant morbidity and mortality among older adults. Detection of pneumococcal carriage is an accepted endpoint in pneumococcal conjugate vaccine studies. However, low sensitivity of culture-based approaches and nasopharyngeal samples have hampered adult S. pneumoniae carriage studies in the past. In contrast, detection of adult S. pneumoniae carriers with qPCR-based approaches can achieve high sensitivity and specifity and qPCR-based testing of oral samples improves accuracy of adult carriage detection. In this Viewpoint we outline a strategy for accurate qPCR-based testing. We recommend a dual-target approach for S. pneumoniae qPCR detection as no genetic target is universally present among or solely unique to it. Furthermore, we advise the evaluation of concordance among quantified qPCR targets to improve the accuracy of S. pneumoniae testing and qPCR-based serotyping. We do not recommend omission of qPCR-based oral sample testing as it will likely result in an underestimation of true adult carrier rates.